Fortification of bakery and corn masa–based foods in Mexico and dietary intake of folic acid and folate in Mexican national survey data. Issue 6 (16th September 2019) - Orjuela, Manuela A; Mejia-Rodriguez, Fabiola; Quezada, Amado D; Sanchez-Pimienta, Tania G; Shamah-Levy, Teresa; Romero-Rendón, Josefina; Bhatt-Carreño, Silvia; Ponce-Castañeda, M Verónica; Castro, Maria A; Paul, Ligi; Villalpando, Salvador
ABSTRACT: Background: In Mexico, wheat and corn flour fortification with folic acid (FA) was implemented in 2001 and mandated in 2008, but without direct enforcement. Current Mexican nutrient-content tables do not account for FA contained in bakery bread and corn masa–based foods, which are dietary staples in Mexico. Objective: The objective of this study was to examine the impact of FA fortification of dietary staples on the proportion of the population consuming below the Estimated Average Requirement (EAR) for folate or above the Tolerable Upper Intake Level (UL) for FA. Methods: We measured FA and folate content in dietary staples (bakery bread and tortillas) using microbial assays and MS, and we recalculated FA intake from 24-h recall dietary intake data collected in the 2012 Mexican National Health and Nutrition Survey (Encuesta Nacional de Salud y Nutrición) utilizing estimates from our food measurements, using nutrient concentrations from tortillas to approximate nutrient content of other corn masa–derived foods. The revised FA intake estimates were used to examine population-level intake of FA and dietary folate equivalent (DFE) accounting for geographic differences in FA content with statistical models. Results: FA content in dietary staples was variable, whereas use of FA-fortified flour in corn masa tortillas increased with population size in place of residence. Accounting for dietary staples' FA fortification increased population estimates for FA and DFE intake, resulting in a lower proportion with intake below the EAR and a higher proportion with intake above the UL. Despite accounting for FA-fortified staple foods, 9–33% of women of childbearing age still have intake below the EAR, whereas up to 12% of younger children have intake above the UL. Conclusions: Unregulated FA fortification of dietary staples leads to unpredictable total folate intake without adequately impacting the intended target. Our findings suggest that monitoring, evaluation, and enforcement of mandatory fortification policies are needed. Without these, alternate strategies may be needed in order to reach women of childbearing age while avoiding overexposing children.